Science Storytelling beyond the Dramatic Arc: Narrativity and Little Red Schoolhouse Principles in Science Communication - Daniel A. Newman (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Narrative is widely recommended for improving science communication, yet the main approach to science storytelling is limited and limiting, advocating fixed dramatic arcs and the ideal of narrativehood, the absolute quality of being a coherent narrative. Neglected by this approach, I argue, are the finer grained linguistic patterns that give texts local narrativity, the quality of being narrative in a scalar, adjectival sense. I harmonize narrativity with the well-established principles of clear technical writing developed by Joseph Williams, then demonstrate how these principles might be used and taught through a comparative reading of several texts discussing a single topic in genres ranging from amateur blogs to specialized scientific journals. The narrativity-based approach has several advantages. It avoids the reductionism of the template-based approach, as well as its questionable dependence on narrative structures derived from the arts and entertainment. In terms of adoption by scientists and other science communicators, the approach also has the advantage of not requiring a radical overhaul of current communicative practices; it also reduces the difference between technical and public-facing writing. In short, the approach proposed here offers a workable and effective way to telling science stories with minimal simplification or distortion of scientific information.